Strengthening Islamic Moral Character In Higher Education: Implementing Ta'līm Al-Muta'allim At Pesma Kh Mas Mansur UMS - Nadya Fatma Febiyana; Muhammad Wildan Shohib (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This study aims to describe the implementation of Ta'lim Muta'alim learning in strengthening the morals of students at the KH Mas Mansur Student Islamic Boarding School (PESMA) and also the educational values ​​in Ta'lim Muta'alim learning. This research is motivated by the increasing phenomenon of moral deviation among students, so that moral development is needed. This study employs a descriptive research design and a qualitative methodology. methods for gathering data through documentation, interviews, and observation. Data analysis involves gathering, reducing, presenting, and deriving conclusions from data. Triangulation of sources and methods is used to test the data's veracity. The study's findings show that Ta'lim Muta'alim learning is implemented at PESMA KH Mas Mansur in three stages: planning, execution, and assessment. In the planning stage, PESMA uses a curriculum based on Muhammadiyah 'Aisyiyah College (PTMA) and Indonesian language teaching materials to be easily understood by students. The implementation stage of learning applies an active learning method that combines lectures, discussions, questions and answers, and role models from teachers. The evaluation was conducted comprehensively, encompassing cognitive, affective, and psychomotor aspects. This study also found that Ta'lim Muta'alim learning contains important educational values, such as morality towards oneself, society, and the environment, which are internalized to shape the character of students with noble character. The implementation of this learning has proven to play a significant role in strengthening the morality of students through the inculcation of moral and spiritual values ​​in everyday life.